THE BURDEN OF INFORMAL CAREGIVERS OF PEOPLE WITH PRESSURE INJURIES IN-HOME CARE (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To identify the overload of informal caregivers of people with pressure injuries in home care. Method: This is a descriptive and cross-sectional study carried out with 29 patients with pressure injuries and 29 informal caregivers, in March 2019, in the interior of São Paulo state, Brazil. An instrument was used to assess the sociodemographic and clinical profile of patients and caregivers, in addition to the Caregiver Burden Scale. Results: People with pressure ulcers were mostly men, elderly and with neurological problems. There was a predominance of female caregivers, with a mean age of 56 years. In the analysis of care overload, the most affected domains were isolation (x = 2.38), followed by general tension (x= 2.31) and disappointment (x = 2.06). The mean total burden was 2.02. As factors contributing to the burden, age, duration of injury, time dedicated to care, degree of kinship between the caregiver and the person with pressure injury and the presence of health problems self-reported by caregivers stood out. Conclusion: Informal caregivers of people with pressure injury have subjective impacts measured by the burden scale, mainly in the domains of isolation, general tension and disappointment, as a result of the involvement of a family member. Understanding the overload experience of care overload can contribute to the development of care strategies for family members/informal caregivers, to reduce the risk of exhaustion and illness.